Indocyanine Green Lymphangiography as an Adjunct for the Optimal Identification and Management of Lymphatic Leaks in the Groin - Rebecca, Alanna M.; Mahabir, Raman C.; Pflibsen, Lacey; Hillberg, Nadine; Jensen, Claire; Casey, William J., III (Journal of Reconstructive Microsurgery, 2019)
Background The treatment of lymphatic leaks and lymphoceles in the groin can be challenging with no optimal management determined to date. We postulate that indocyanine green (ICG) lymphangiography improves visualization of the site of a lymphatic leak and can optimize their management.Methods A retrospective review was conducted of all cases in which ICG lymphangiography was used in the management of lymphatic leaks in the groin over an 18-month span. The inciting surgical procedure resulting in the leak was determined. Following thorough debridement, ICG was injected intradermally in the distal extremity and the site of the lymphatic leak was documented (superficial or deep) and oversewn. Outcomes were reported with regard to healing, infection, time to drain removal, and adjunctive procedures.Results Fifteen patients underwent ICG lymphangiography during the surgical treatment of a lymphatic leak in the groin during the study period. In all cases, the site of the lymphatic leak was accurately identified and oversewn. In eight cases, the site of the lymphatic leak was in the subcutaneous tissue superficial to the femoral vessels rather than medial to the femoral vessels in the area of the lymph node basin. A local muscle flap was used in 10 cases simultaneously. All wounds healed primarily without an associated wound or infection.Conclusion ICG lymphangiography facilitated the identification of lymphatic leaks in the groin and optimized their management in these challenging cases, many of which may have been missed if the area around the inguinal lymph node basin was treated exclusively.
Keywords: ICG lymphangiography; lymph leak; lymphoceles